Philosophical and theological writings - Lessing, Gotthold Ephraim, 1729-1781 (Cambridge University Press, 2005)
This volume presents the most comprehensive collection to date in English of Lessing's philosophical and theological writings, several of which appear here in English for the first time. They are translated and edited by H.B. Nisbet, who also provides an introduction that sets them in their historical and philosophical contexts.
Keywords: Leibniz, Gottfried Wilhelm, -- Freiherr von, -- 1646-1716.; Philosophical theology.; Protestant churches -- Doctrines -- Early works to 1800.; Philosophy, German -- 18th century -- Early works to 1800.; Philosophical anthropology -- Early works to 1800.; Églises protestantes -- Doctrines -- Ouvrages avant 1800.; Philosophie allemande -- 18e siècle -- Ouvrages avant 1800.; Anthropologie philosophique -- Ouvrages avant 1800.; Théologie philosophique.; PHILOSOPHY -- History & Surveys -- Modern.; Protestant churches -- Doctrines; Philosophy, German; Philosophical anthropology; Philosophical theology; 1700-1799; Early works